Identifikasi Kandidat Microservices Dengan Analisis Domain Driven Design - Juliawan Pawana, I Wayan Adi; Wiharta, Dewa Made; Sastra, Nyoman Putra (Majalah Ilmiah Teknologi Elektro, 2021)
This study aims to identify microservices in sistem informasi dosen (SIMDOSEN) of udayana university using Domain Driven Design analysis. SIMDOSEN was developed with a monolithic architecture and has several modules including lecturer data management module, lecturer history, management of tridharma perguruan tinggi activities, lecturer performance targets, etc. Dynamic policy changes cause the system to be difficult to adapt to accommodate needs and lack of documentation cause different interpretations of system function between programmers. With microservices, the system will be split into several services using a RESTful API which is documented using OpenAPI Specifications so that it is hoped that the development of SIMDOSEN will be more adaptive to changes in system requirements and reduce misunderstanding between programmers in the future .